The relationship between economic growth and inflation rate of Lao PDR - Chitthaphone, Sonepeth; CHANTHAVONE, Thongphanh; XIONGTOUAD, Tongvang; HER, Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to analyze the relationship between the economic growth rate and the inflation rate by using the VAR model and the Granger causality test using time series data from 1996-2023. The results of the study show that the economic growth rate of the previous year has the strongest effect on the economic growth rate of the current year and has a positive effect with a statistically significant period and a significance level of 0.01. The inflation rate has a different effect. The inflation rate has a different effect. The inflation rate in the previous year has a positive effect, while the inflation rate at lag 2 has a negative effect with a statistical significance level of 0.01 and 0.05 respectively. It is also found that the economic growth rate at lag 1 has the largest effect and has a negative effect on the inflation rate in the current year with a significance level of 0.01. While the inflation rate has a statistically significant impact on the inflation rate in the current year at a different level, lag 2 is statistically significant. The causality test has shown that the relationship between economic growth and the inflation rate is bidirectional, i.e. the inflation rate has an impact on economic growth and, conversely, economic growth also has an impact on the inflation rate, with statistical significance levels of 0.05 and 0.01 respectively. Based on the results, we suggest that the relevant parties must make serious and urgent efforts to solve the problem of inflation in Lao PDR at an appropriate level in order to create a good environment for the sustainable development of Lao PDR.